2015
DOI: 10.1007/s00127-015-1078-2
|View full text |Cite
|
Sign up to set email alerts
|

Social networks, mental health problems, and mental health service utilization in OEF/OIF National Guard veterans

Abstract: General social support and military-specific support were robustly associated with reduced mental health symptoms in National Guard members. Policy makers, military leaders, and clinicians should attend to service members' level of support from both the community and their units and continue efforts to bolster these supports. Other strategies, such as focused outreach, may be needed to bring National Guard members with need into mental health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 110 publications
0
20
0
Order By: Relevance
“…The combination of substance use, unemployment, life-time arrests, and restoration of peers and relationship building may warrant a further review in order to provide similar Veterans a successful treatment experience. Sripada et al (2015) similarly found that general social support was correlatedwith reduced mental health symptoms. Slattery,Dugger, Lamb, and Williams (2013) suggest that one reason for VTC success is the restoration of peers-both in treatment and in the community, particularly peer mentors.…”
Section: Discussionmentioning
confidence: 87%
“…The combination of substance use, unemployment, life-time arrests, and restoration of peers and relationship building may warrant a further review in order to provide similar Veterans a successful treatment experience. Sripada et al (2015) similarly found that general social support was correlatedwith reduced mental health symptoms. Slattery,Dugger, Lamb, and Williams (2013) suggest that one reason for VTC success is the restoration of peers-both in treatment and in the community, particularly peer mentors.…”
Section: Discussionmentioning
confidence: 87%
“…Barriers to accessing traditional psychological treatments include a lack of trained interventionists, limited insurance coverage and infrastructure, inequitable distribution of services, geographic isolation, lack of evidence-based protocols used by clinicians, social stigma associated with help-seeking, and lack of cultural appropriateness and acceptability of mental health care generally [11][12][13][14][15]. An epidemiological study in the US suggested that only 53% of individuals with a history of PTSD had received any type of treatment [16]. Low service utilization rates are also evident in lowand middle-income countries; a study in the Eastern Cape Province of South Africa found that just under half of those who qualified for PTSD had accessed health care services [17].…”
Section: Access To Treatmentmentioning
confidence: 99%
“…Studies have also looked at social support and unit support as enabling factors (Sripada et al. ). While there is a great deal of evidence suggesting a link between social support and lower likelihood of mental health conditions (Sripada et al.…”
Section: Mental Health Needmentioning
confidence: 99%
“…Studies have also looked at social support and unit support as enabling factors (Sripada et al 2015). While there is a great deal of evidence suggesting a link between social support and lower likelihood of mental health conditions (Sripada et al 2015), the evidence that social support increases the likelihood that Guard soldiers will access mental health treatment is less robust. However, these enabling factors should be investigated among Guard soldiers as potential contributors to VA and non-VA mental health service use.…”
Section: Enabling Factorsmentioning
confidence: 99%